Rice Market Integration in Lampung Province - Irmayani Noer (Politeknik Negeri Lampung, 2014)
The price of rice depends on the relative influence of certain market and the mechanism of price transmission of one market to another (farm gate market system). The analysis of market integration can be obtained through some measurements among others by price correlation and price transmission analyses. This research is to analyze the integration of free market in some districts of Lampung Province. The samples are two regions which are Central Lampung, which is the production center, and Bandar Lampung as the center of consumers market. The data used are monthly time sequel data provided by the Food Crops and Horticulture Office and the result of observation in some markets both in Central Lampung and Bandar Lampung. The data related to price of rice in the markets were obtained from the markets in the two regions within 2009 until 2011.Based on the analyses, the correlation price of rice in producer and consumer levels in Lampung Province indicated by the value of price transmission is bigger than one. This indicates that if there is a price of rice change in the level of retailers as big as one percent, it will be followed by the changes as big as 1,783 % in the farmers. It also means that the changes in the level of farmers are slightly bigger than the price in retailers. The value of the correlation analyses of free market of rice indicated by IMC is 0.415. This indicates that integration level of both markets is relatively high. If IMC < 1 or close to zero, the market integration level will be higher. The market in farmers level and retailers in Lampung Province appears to have high level of integration. Key words: rice market, market integration